2021
DOI: 10.1016/j.molp.2021.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of lateral root formation through single-cell RNA sequencing reveals order of tissue initiation

Abstract: Postembryonic organogenesis is critical for plant development. Underground, lateral roots (LRs) form the bulk of mature root systems, yet the ontogeny of the LR primordium (LRP) is not clear. In this study, we performed the single-cell RNA sequencing through the first four stages of LR formation in Arabidopsis. Our analysis led to a model in which a single group of precursor cells, with a cell identity different from their pericycle origins, rapidly reprograms and splits into a mixed ground tissue/stem cell ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 67 publications
1
36
0
Order By: Relevance
“…Interestingly, we identified the QC-like cells at the intermediate stage of redifferentiation, and the considerably increased expression of well-known QC regulator, WOX5 , in this cell cluster further supported the QC-like cell identity. Consistently, QC-like cells, which have been suggested to be primarily responsible for organ regeneration 10 , have also been identified during lateral root formation 21 . QC cells are the core cells of Root apical meristem (RAM) and could generate diverse root cell types 55 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, we identified the QC-like cells at the intermediate stage of redifferentiation, and the considerably increased expression of well-known QC regulator, WOX5 , in this cell cluster further supported the QC-like cell identity. Consistently, QC-like cells, which have been suggested to be primarily responsible for organ regeneration 10 , have also been identified during lateral root formation 21 . QC cells are the core cells of Root apical meristem (RAM) and could generate diverse root cell types 55 .…”
Section: Discussionmentioning
confidence: 78%
“…Recent advances in single-cell RNA sequencing (scRNA-seq) technology provide unprecedented opportunities for systematically identifying cellular and molecular differentiation trajectories of plant regeneration at the single-cell level 17,18 . The scRNA-seq technique has been widely used in plant development studies, facilitating reconstructing the development trajectories and establishing gene expression regulatory networks of root epidermis 19,20 , lateral root development 21-28 , shoot apex 29,30 , leaf phloem cells 31,32 , guard cells 33,34 , seedlings 35 and callus 10 , demonstrating its advantages in discovering regulatory elements 36 . Up to now, scRNA-seq has not been used to analyze the complex shoot regeneration process in Arabidopsis .…”
Section: Introductionmentioning
confidence: 99%
“…Our results support that the position of the LR QC is set before emergence but only activated post-emergence as it had been suggested earlier (Celenza et al ., 1995; Malamy and Benfey, 1997). A recent single cell analysis of the developing LR has shown that expression of genes typically associated with the QC in the primary RAM can be readily detected in stages I to III LR, yet distributed amongst different clusters that only form a distinct coherent population at later stages (Serrano-Ron et al ., 2021). Our observation of WOX5-YFP expression in most cells of stage II LR supports this notion of a progressive specification of cell identities in the early phases of LR organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupting SCR function perturbed the formation of these QC precursor cells (Goh et al ., 2016). A recent analysis of LR formation at single cell resolution (Serrano-Ron et al ., 2021) revealed that although expression of QC markers debuts early during LR formation they are distributed amongst different cell populations and a distinct coherent population only emerges at later stages.…”
Section: Introductionmentioning
confidence: 99%
“…Several of the selected top candidate genes influenced lateral root development when their expression was manipulated in validation experiments. Other groups have tackled low abundance cell types in even higher resolution, focusing on LRP in Arabidopsis ( Serrano-Ron et al, 2021 ), shoot-borne-root meristems in tomato ( Omary et al, 2020 ), inflorescence tissue in maize ( Xu et al, 2021 ), and phloem root cells in Arabidopsis ( Roszak et al, 2021 ).…”
Section: Capturing Low-abundance Cellsmentioning
confidence: 99%